Ecological certification of forest products: economic challenges - Kiker, C.F.; Putz, F.E. (1997)
With increasing rates of forest depletion worldwide, it is increasingly being asked whether markets can play a role in mitigating the deleterious environmental and social impacts of forestry activities. The Forest Stewardship Council and others have proposed systems of ecological certification, where otherwise very similar products are viewed by consumers as different products because additional information on the products' history is provided. The certification assures the consumer that the products have been produced with practices that meet fundamental ecological and social standards. For ecological certification systems to be viable and deliver products to the market over the long term, the relationships among key components must evolve economically and institutionally. Consisting of local forest management firms, local certifying non-governmental organizations, international non-governmental organizations, timber and product markets, the ecological certification system transcends local forests and communities to international markets. Conceptually, the system is a series of principal-agent relationships. This paper, in addition to developing the concept of ecological certification, analyses the relationships among the many actors and the relationship of the actors to the forest.